2008
DOI: 10.1002/adfm.200800531
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin‐CdTe‐CaCO3@Polyelectrolytes 3D Architecture: Fabrication, Characterization, and Application in Biosensing

Abstract: A Hemoglobin‐CdTe‐CaCO3@polyelectrolyte 3D architecture is synthesized by a stepwise layer‐by‐layer method and is further used to fabricate an electrochemistry biosensor. While the calcium carbonate (CaCO3) microsphere acts as an effective host for the loading of cadmium telluride (CdTe) quantum dots due to its channel‐like structure, the polyelectrolyte layers further increase the loading amount and help in the formation of a thick and uniform quantum‐dot “shell”, which not only improves the stability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 31 publications
1
30
1
Order By: Relevance
“…At pH 7.0, the linear range of the H 2 O 2 sensor was from 0.5 to 115 mm, with a correlation coefficient of 0.9988 (inset in Figure 7), which is much wider than that (from 5 to 45 mm) of a reported biosensor. [40] The detection limit with a signal-to-noise ratio of three was estimated to be 0.12 mm, which is lower than the level of 1.4 mm reported for a (PDDA/Fe 3 O 4 NPs) 5 multilayer modified electrode. [41] For comparison, the amperometric responses of l-HCNTs/GCE and MWCNTs/ GCE are shown in Figure 7(curves b and c).…”
Section: More Importantly We Compared the Catalytic Efficiencies Of mentioning
confidence: 98%
“…At pH 7.0, the linear range of the H 2 O 2 sensor was from 0.5 to 115 mm, with a correlation coefficient of 0.9988 (inset in Figure 7), which is much wider than that (from 5 to 45 mm) of a reported biosensor. [40] The detection limit with a signal-to-noise ratio of three was estimated to be 0.12 mm, which is lower than the level of 1.4 mm reported for a (PDDA/Fe 3 O 4 NPs) 5 multilayer modified electrode. [41] For comparison, the amperometric responses of l-HCNTs/GCE and MWCNTs/ GCE are shown in Figure 7(curves b and c).…”
Section: More Importantly We Compared the Catalytic Efficiencies Of mentioning
confidence: 98%
“…For practical use in biomedical applications, including toothpastes, cosmetics, protein encapsulation, and biosensing, the structural stability of CaCO3 in aqueous solutions is highly desired [7,[27][28][29]. Previous research showed that porous vaterite samples in the absence of stabilizing additives would convert easily to non-porous rhombohedral calcite under ambient conditions [14].…”
Section: Synthetic Route and Structural Characterizations Of Pcmssmentioning
confidence: 99%
“…On the one hand, QDs can be simply mixed with proteins to make a protein -QD -modifi ed electrode. On the other hand, QDs can be stabilized with thioglycolic acid ( TGA ) or 3 -mercaptopropionic acid to form an anionic surface [4,5] . These stabilized QDs can form strong electrostatic interaction with proteins by the anionic groups on the QDs and cationic groups on the proteins.…”
Section: Attachment Of Biomolecules To Quantum Dotsmentioning
confidence: 99%
“…The third kind of H 2 O 2 biosensor, based on the Hb -immobilized on CdTeCaCO 3 @polyelectrolyte three -dimensional architecture, was prepared by a stepwise layer -by -layer method shown in Figure 10.6 [5] . First, polyelectrolyte layers poly(sodium 4 -styrenesulfonate)/poly(allylamine hydrochloride) ( PSS / PAH ) were assembled onto the CaCO 3 microsphere, which acts as an effective host for the loading of CdTe QDs due to its channel -like structure and the strong electrostatic interaction between the cationic groups ( -NH 3 + ) of the PAH and the negatively charged carboxy ( -COO − ) groups on the surface of CdTe QDs.…”
Section: Hemoglobin -Quantum Dot -Based H 2 O 2 Biosensormentioning
confidence: 99%